Hubungan Tingkat Pengetahuan Prediabetes dengan Obesitas - Alfiyya Nur Mahdiyyah; Noormartany; Triyani, Yani (Bandung Conference Series: Medical Science, 2024)
Abstract. Prediabetes is an important health problem today. Risk factors that can cause the progression of prediabetes to diabetes mellitus are obesity as measured by body mass index and waist circumference. The aim of this study was to assess knowledge about prediabetes with body mass index and waist circumference in first year students at the Faculty of Medicine, Bandung Islamic University for the 2022/2023 academic year. The design used was cross-sectional with 164 respondents. The research used was analytical observational. Data were collected using Google Form regarding awareness and knowledge questionnaires about prediabetes, with a total of 29 validated questions. Other important data that is measured directly is body weight, height and waist circumference. Of the 164 respondents, the majority were 18 years old, 54.9%, and 62.2% female; while height 151-160 cm is 43.3% and weight is in the obesity category 37.8%. Normal waist circumference for men is 23.8% and 39% for women. Respondents had good knowledge about prediabetes 45.1%. Based on the Pearson's chi-square test, the values obtained were p=0.883 (p>0.05) and p=0.105 (p>0.05). This means that there is no relationship between knowledge of prediabetes and obesity as measured by body mass index and waist circumference. Abstrak. Pradiabetes merupakan masalah kesehatan yang penting saat ini. Faktor risiko yang dapat menyebabkan progesivitas prediabetes menjadi diabetes melitus adalah obesitas yang diukur dengan Indeks massa tubuh dan lingkar pinggang. Tujuan penelitian ini menilai pengetahuan tentang pradiabetes dengan indeks massa tubuh dan lingkar pinggang pada mahasiswa tingkat satu Fakultas Kedokteran Universitas Islam Bandung tahun Ajaran 2022/2023. Desain yang digunakan adalah cross-sectional dengan 164 responden. Penelitian yang digunakan adalah observasional analitik. Data yang dikumpulkan menggunakan Google Form mengenai kuesioner kesadaran dan pengetahuan tentang pradiabetes, dengan total 29 pertanyaan yang divalidasi. Data penting lainnya yang diukur langsung, yaitu berat badan, tinggi badan, dan lingkar pinggang. Dari 164 responden mayoritas berusia 18 tahun 54,9%, dan perempuan 62,2%; sedangkan tinggi badan 151-160 cm 43,3% dan berat badan berkategori obesitas 37,8%. Lingkar pinggang normal laki-laki 23,8% dan perempuan 39%. Responden berpengetahuan baik tentang pradiabetes 45,1%. Berdasarkan uji Pearson’s chi-square diperoleh nilai p=0,883 (p>0,05) dan p=0,105 (p>0,05). Dapat disimpulkan tidak ada hubungan antara pengetahuan pradiabetes dan obesitas yang diukur indeks massa tubuh dan lingkar pinggang.